Development of Heat Resistant Emulsion Explosives - Tetsuya Sawada; Koichi Kurokawa; Fumihiko Sumiya; Yukio Kato (International Society of Explosives Engineers, 1992)
In some metal mines, it is a serious problem the decomposition of explosives which occurs suddenly by contact with ore containing pyrites under high temperature conditions. In the present paper, we investigated heat resistant properties of emulsion explosives and other industrial explosives by contact with ore containing pyrites under high temperature conditions.